The Recovery Paradox in Latin America and the Caribbean Growth Amid Persisting Structural Problems - Economic Commission for Latin America; the Caribbean (United Nations, 2021)
This Special Report examines the economic and social impact of the COVID-19 pandemic, more than a year after it first appeared, providing new growth projections for the region’s countries. The document, entitled The recovery paradox in Latin America and the Caribbean. Growth amid persisting structural problems: inequality, poverty and low investment and productivity, analyzes the performance of the region’s main economic and social indicators and presents policy proposals for achieving a transformative recovery based on the forging of a new development pattern.